Default Mode Network Efficiency Is Correlated With Deficits in Inhibition in Adolescents With Inhalant Use Disorder - Hernández-Álvarez, Dailett M.; Pacheco, Lucero; Velasco-Segura, Roberto; Pérez de la Mora, Miguel; Tejeda-Romero, Claudia; González-García, Nadia (Frontiers in Psychiatry, 2020)
It is well established that alterations in cognitive function and damage to brain structures are often found in adolescents who have substance use disorder (SUD). However, deficits in executive cognitive functioning in adolescents related to the vulnerability and consumption of such substances are not well known. In this study, we use graph theoretic analysis to compare the network efficiency in the resting state for three networks—default mode network (DMN), salience network (SN) and fronto-parietal network (FPN)—between inhalant-consuming adolescents and a control group (12 to 17 years old). We analysed whether the efficiency of these functional networks was related to working memory, mental flexibility, inhibition of response and sequential planning. We found that, when compared to the control group, inhalant-consuming adolescents presented with important deficits in communication among brain regions that comprise the DMN, SN and FPN networks. DMN is the most affected network by inhalant abuse during adolescence. The mediation analyses suggested that the relationship between inhalant abuse and inhibitory control and sequential planning was partly mediated by DMN efficiency.